Dialogue on the Stakeholder Theory of the Corporation: Concepts, Evidence, and Implications - Jacobs, David C.; Getz, Kathleen A. (Academy of Management Review, 1995)
The article presents a response to an earlier article in “Academy of Management Review” regarding the stakeholder theory of the corporation from Thomas Donaldson and Lee Preston. The authors take issue with the foundation of the argument, claiming that the theory loses force and clarity when presented as a descriptive model. The article further discusses the issue of property as a basis for stakeholder theory, and illustrates the instability of this foundation through recent and current legal actions. The authors present other ethical theories that might act as a normative basis for stakeholder theory.